2019
DOI: 10.1111/psyp.13341
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and biological responses to acute stress in people with Type 2 diabetes

Abstract: Loneliness is linked with all‐cause mortality and coronary heart disease. Altered neuroendocrine and inflammatory responses to stress constitute potential pathways linking loneliness and ill‐health. Stress responsivity is modified in people with Type 2 diabetes, but it is unclear whether loneliness influences biological stress responses in this population. We assessed interleukin‐6 (IL‐6), interleukin‐1 receptor antagonist (IL‐1RA), monocyte chemoattractant protein‐1 (MCP‐1), and cortisol responses to acute st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 63 publications
3
22
4
Order By: Relevance
“…Loneliness is also associated with inflammation [36], which is of relevance to type 2 diabetes as pooled evidence suggests that heightened inflammation is a risk factor for the condition [37]. Indeed, loneliness has been associated with heightened inflammation in laboratory settings in people with diagnosed type 2 diabetes [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loneliness is also associated with inflammation [36], which is of relevance to type 2 diabetes as pooled evidence suggests that heightened inflammation is a risk factor for the condition [37]. Indeed, loneliness has been associated with heightened inflammation in laboratory settings in people with diagnosed type 2 diabetes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol plays an important mechanistic function related to type 2 diabetes [ 7 ] and dysregulation in daily cortisol output is predictive of new onset pre-diabetes and type 2 diabetes [ 34 ]. In samples with overt type 2 diabetes, loneliness has been associated with dysregulation in cortisol responses to acute laboratory stress [ 35 ]. Loneliness is also associated with inflammation [ 36 ], which is of relevance to type 2 diabetes as pooled evidence suggests that heightened inflammation is a risk factor for the condition [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the relationships between loneliness and metabolic control indicators. Available studies indicate that HbA1c and BMI were the most common metabolic control indicators assessed in relation to loneliness [ 12 , 14 , 21 , 22 ]. An assessment of the relationship between loneliness and treatment adherence in diabetic patients showed a correlation between loneliness and postprandial blood glucose levels in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to our study, no correlation was shown between HbA1c and BMI [ 21 ]. Also, no relationship was demonstrated between loneliness and these indicators in a study assessing the severity of already impaired response to stress in T2DM patients [ 14 ]. Although the relationship between loneliness and long-term control of glucose levels assessed based on HbA1c was not confirmed by Niemcryk [ 22 ], the importance of loneliness in T2DM patients in terms of following a healthy diet was confirmed during an attempt to identify predictors of long-term blood glucose control [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation